2002
DOI: 10.1021/ac010979m
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Analysis of Low-Mass Molecules by MALDI-TOF Mass Spectrometry

Abstract: We report a novel method termed matrix suppressed laser desorption/ionization to improve the analysis of low-mass molecules by MALDI-TOF mass spectrometry. In this method, the surfactant of cetrimonium bromide (CTAB) is added to the conventional matrix of r-cyano-4-hydroxycinnamic acid solution to prepare the MALDI samples. During the MALDI process, the presence of CTAB could substantially or even completely suppress the matrixrelated ion background. As a result, very clean mass spectra can be routinely obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
143
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 25 publications
6
143
0
Order By: Relevance
“…However, it is difficult to analyze small molecules with conventional matrix due to matrix ion interference. Recently, porous silicon [12][13][14][15], matrix with high molecular weight [16,17], surfactant-suppressed matrix [18], and inorganic materials [19][20][21] have been successfully employed in the analysis of small molecules. However, there are no reports about the analysis of nonpolar PAHs by MALDI-TOF due to their great difficulty in ionization, though metal-assisted LDI analysis of nonpolar polyethylene was reported [22].…”
mentioning
confidence: 99%
“…However, it is difficult to analyze small molecules with conventional matrix due to matrix ion interference. Recently, porous silicon [12][13][14][15], matrix with high molecular weight [16,17], surfactant-suppressed matrix [18], and inorganic materials [19][20][21] have been successfully employed in the analysis of small molecules. However, there are no reports about the analysis of nonpolar PAHs by MALDI-TOF due to their great difficulty in ionization, though metal-assisted LDI analysis of nonpolar polyethylene was reported [22].…”
mentioning
confidence: 99%
“…Although many groups have demonstrated that the use of an organic chemical matrix in MALDI-TOF-MS is capable of detecting peptides, proteins, and nucleic acids [2], there are still unresolved problems in the general application of MALDI-TOF-MS: (1) The cocrystallization of analytes with matrices does not produce homogeneous mixtures, which cause hot spots and thereby require sweet-spot searching [3]. (2) MALDI-TOF-MS is incapable of detecting small molecules because of the high background signals of small organic matrices, which are present in the low-mass region (Ͻ500 Da) [4]. (3) The presence of salts in a sample solution will increase the intensities of salt-adducted forms [5].…”
mentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35] Recent works dealing with the use of the technique to the identification and structural analysis of various compounds can be mentioned. [36][37][38][39][40][41][42][43][44][45][46][47][48] Coupling of MALDI with liquid chromatography, capillary electrophoresis (CE) and gel chromatography is a way to extend its applicability. 32,[49][50][51][52][53][54][55][56][57][58] The possibility to attain the sensitivity of physical limits (a few atoms or molecules) by laser-assisted reflectron TOF-MS has been stated.…”
Section: An Overview Of Analytical Applications Of Tof-ms Analyzersmentioning
confidence: 99%